Implementing global strategies: The role of procedural justice - Kim, W. Chan; Mauborgne, Renée (Strategic Management Journal, 1991)
While work in the field of global strategic management has largely focused on defining the content of effective global strategies and on prescribing winning strategic moves for multinationals, this research argues the importance of the process through which global strategies are generated, in particular the perceived procedural justice of that process. Drawing on the theoretical heritage of justice-based research, this study first explored the meaning of procedural justice by an investigation of the specific criteria used by subsidiary top managers to define what they perceive to be a fair process in global strategy-making. Second, the importance of procedural justice was assessed by an examination of its effects on the higher-order attitudes of commitment, trust, and social harmony as well as on the lower-order attitude of outcome satisfaction in subsidiary top management. One of the central conclusions of the research is that the procedural justice of the global strategy generation process indeed affects commitment, trust, and social harmony as well as outcome satisfaction in subsidiary top management, and hence provides a potentially powerful but, as yet, unexplored avenue for mobilizing the multinational's global network of subsidiaries.